Harvesting Criteria and Drying Methods to Improve the Quality of Foxtail Millet Seeds (Setaria italica L. Beauv.) - Lainufar, Putri Aulia; Qadir, Abdul; Suhartanto, M. Rahmad; Ardie, Sintho Wahyuning (Journal of Tropical Crop Science, 2021)
Foxtail millet is annual grasses with grains that are smaller than those of sorghum, rice, and wheat, and is considered one of the minor economic crops but with nutritional values similar to other major food crops. The development of millet as major cereal crop is considered challenging due to the low quality of its seeds, and studies have been conducted to improve millet’s seed quality. We conducted this study to determine the harvesting criteria of foxtail millet seeds based on the change in color of the panicles. We also wanted to determine the drying treatment, and evaluate the relationship between the position of the seed on the panicles and the seed viability and vigor. The first experiment was arranged based on a completely randomized design with panicle color as the first factor (green, yellow 75%, and brown) and drying time as the second factor (0 hours, 24 hours, 48 hours, 72 hours). The second experiment was arranged in a completely randomized design with seed position as the main factor (base, middle, tip). The study was conducted on two genotypes of millet, i.e. “BOTOK 4” and “BOTOK 10”. The highest seed quality of “BOTOK 4” and “BOTOK 10” genotypes were obtained when the panicles were brown and dried for 72 hours; the seed chlorophyll content was the lowest and water content was 8.88%, with the highest viability and vigor, i.e., germination rate of 88.3%-90%, maximum growth potential of 92%-95.3%, normal sprout dry weight 596-620 mg, vigor index of 33.6% - 21.6%, and growth rate of 18.2%-17.1% etmal-1. The highest seed viability and vigor in “BOTOK 4” genotypes were obtained from the base position, i.e., 78.7% germination rate, maximum growth potential of 83.7%, vigor index of 56.5%, growth speed of 19.6 etmal-1, normal sprout dry weight of 48 mg, radicle length of 3.3 cm) and “BOTOK 10” genotypes from the middle position with 91.5% germination, maximum growth potential of 97.2%, vigor index of 21.7%, growth speed of 17.0% etmal-1, and normal sprout dry weight 61 mg.